Bacteraemia, Malaria, and Case Fatality Among Children Hospitalized With Fever in Dar es Salaam, Tanzania - Moyo, Sabrina J.; Manyahi, Joel; Blomberg, Bjørn; Tellevik, Marit Gjerde; Masoud, Nahya Salim; Aboud, Said; Manji, Karim; Roberts, Adam P.; Hanevik, Kurt; Mørch, Kristine; Langeland, Nina (Frontiers in Microbiology, 2020)
Background: Febrile illness is the commonest cause of hospitalization in children <5 years in sub-Saharan Africa, and bacterial blood stream-infections and malaria are major causes of death. Methods: From March 2017 to July 2018, we enrolled 2226 children aged 0-5 years hospitalized due to fever in four major public hospitals of Dar es Salaam namely; Amana, Temeke and Mwananyamala Regional Hospitals and Muhimbili National Hospital. We recorded social demographic and clinical data, performed blood-culture and HIV-antibody testing. We used qPCR to quantify Plasmodium falciparum parasitaemia and Matrix-Assisted Laser Desorption/Ionization-Time of Flight (MALDI-TOF) to identify bacterial isolates. Disk diffusion method was used for antimicrobial susceptibility testing. Results: Nineteen percent of the children (426/2226) had pathogens detected from blood. Eleven percent (236/2226) of the children had bacteraemia/fungaemia and 10% (204/2063) had P. falciparum malaria. Ten children had concomitant malaria and bacteraemia. Gram-negative bacteria (64%) were more frequent than Gram-positive (32%) and fungi (4%). Over fifty percent of Gram-negative bacteria were extended-spectrum beta-lactamase (ESBL) producers and multidrug resistant. Methicillin resistant Staphylococcus aureus (MRSA) was found in 11/42 (26.2%). Malaria severity was associated with high parasitaemia (>four million genomes/µL) of P. falciparaum in plasma. Overall, in-hospital death was 4% (89/2146) and it was higher in children with bacteraemia (8%, 18/227) than malaria (2%, 4/194, P=0.007). Risk factors for death were bacteraemia (p=0.02), unconsciousness at admission (p<0.001) and admission at a tertiary hospital (p=0.003). Conclusions: Our study showed that bacteria and malaria contributed equally in causing blood stream infection (BSI), but bacteraemia caused higher in-hospital death. P. falciparum parasitaemia measured by qPCR is associated with clinical malaria severity. Antimicrobial resistance is rampant amongst the bacterial isolates which stresses the importance of strengthening diagnostic tools and antimicrobial stewardship programs.